The Quality of the Footwear that Appears on the European Single Market in the Context of Its Effect on Consumer Health and Safety. Part 1 - Elżbieta BIELAK (Communications of International Proceedings, 2021)
Despite of continuously conducted research aimed at improving footwear materials properties, the issue of footwear quality with respect to consumer safety may still raise doubts. In this paper the notifications to the Rapid Alert System for Dangerous Non-Food Products (RAPEX) referred to footwear, and recorded in the years 2004-2020 are analysed, which allowed identification of types of potential risks posed to consumers. The most common risk associated with the presence of harmful chemical substances in too large amounts in footwear materials was identified. This risk was discussed in detail, while considering types of substances, its effect on consumer health and safety as well as the REACH regulation guidelines. The results of analysis indicate that footwear approved for sale not always meets the requirements of regulations for ensuring safety of its users, primarily regarding to the content of chemicals e.g. chromium VI, dimethyl fumarate in footwear materials, therefore it may pose health hazards. Although a decreasing tendency for footwear notified to the RAPEX is observed after 2013, the problem is still up to date.
Keywords: Consumer safety; Health; Footwear quality; RAPEX; Hazardous chemicals.